2023
DOI: 10.1039/d2py01478e
|View full text |Cite
|
Sign up to set email alerts
|

Facile grafting modification of main-chain-type semi-fluorinated alternating fluoropolymersviasimultaneous CuAAC reaction and ATRP in one pot at ambient temperature

Abstract: Grafting modification is a useful strategy to endow new functions to fluoropolymers with fluorinated backbone and expand their potential application fields. Herein, we reported a facile method to synthesize graft...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…For example, our group reported the post-modification by using end-group iodine of bipolymers to synthesize block copolymers 35 and grafting copolymers by the periodic iodine atoms. 58 Bao and Wan et al also reported excellent synchronized polymerization and modification in one step polymerization between diiodo and diene monomers. 59 In this work, the periodic iodine atoms on the terpolymer chains were replaced with hydrogen atoms by reduction with AIBN and tributyltin hydride, and the corresponding T g of the modified terpolymers with the removal of iodine atoms (termed SFAT-I) was significantly enhanced, such as 11 °C (SFAT-2) vs. 94 °C (SFAT-I-2), 17 °C (SFAT-3) vs. 85 °C (SFAT-I-3), and 22 °C (SFAT-4) vs. 96 °C (SFAT-I-4), as shown in Fig.…”
Section: Polymer Chemistry Papermentioning
confidence: 97%
“…For example, our group reported the post-modification by using end-group iodine of bipolymers to synthesize block copolymers 35 and grafting copolymers by the periodic iodine atoms. 58 Bao and Wan et al also reported excellent synchronized polymerization and modification in one step polymerization between diiodo and diene monomers. 59 In this work, the periodic iodine atoms on the terpolymer chains were replaced with hydrogen atoms by reduction with AIBN and tributyltin hydride, and the corresponding T g of the modified terpolymers with the removal of iodine atoms (termed SFAT-I) was significantly enhanced, such as 11 °C (SFAT-2) vs. 94 °C (SFAT-I-2), 17 °C (SFAT-3) vs. 85 °C (SFAT-I-3), and 22 °C (SFAT-4) vs. 96 °C (SFAT-I-4), as shown in Fig.…”
Section: Polymer Chemistry Papermentioning
confidence: 97%
“…The fluorinated alkyl iodide formed in a chain end allows extension to block copolymers, and alkyl iodide groups on the backbone could be converted into other functionalities to yield grafted copolymers. [39] Taken together, the advancements of photoredox CRCPs of fluoroalkenes and vinyl comonomers shed new light on the controlled synthesis of main-chain fluoropolymers, enabling facile, efficient and on-demand accesses toward a variety of well-defined structures by exposing to light irradiation. However, there are still concerns to be explored during expanding the use of such methods, for instance, 1) the preparation of high-molecular-weight mainchain fluoropolymers remain difficult, 2) expandability of this strategy toward more fluoroalkenes has yet to be disclosed, 3) essential properties of novel structures are valuable to showcase the interests of the well-defined fluoropolymers.…”
Section: Minireviewsmentioning
confidence: 99%
“…Cheng et al proposed a novel strategy for the synthesis of fluorinated alternating copolymers via the step transfer-addition and radical-termination (START) polymerization of α,ω-diiodoperfluoroalkanes and α,ω-unconjugated dienes. [30][31][32][33][34] In this strategy, the C-I bond of the α,ω-diiodoperfluoroalkane was cleaved to generate -CF 2…”
Section: Introductionmentioning
confidence: 99%
“…With functionalized dienes as the monomers, a series of fluorinated polyolefins, 35,36 polyethers, 37 polyesters, 32,35 and polyether esters 38,39 have been successfully synthesized. Moreover, they also prepared fluorinated block copolymers [40][41][42][43] and graft copolymers [44][45][46] taking advantage of the reactive iodine group on the polymer backbone and terminals. The success of START polymerization has therefore demonstrated the potential of the synthesis of fluorinated polyesters by combining step-growth polymerization and chain-growth polymerization mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation